Factors Affecting Under-five Mortality in Selected Districts of Nepal: A Cross-sectional Study Using Logistic Regression - Bhusal, Madhav Kumar; Khanal, Shankar Prasad (Nepalese Journal of Statistics, 2025)
Background: Despite the considerable improvement in reducing under-five mortality (U5M) over time, Nepal has been experiencing a slow decline in under-five mortality rates and stationary neonatal mortality rates in recent years. It reflects the ongoing challenges to meet the Sustainable Development Goals target of reducing the under-five mortality rate to 25 or fewer per 1,000 live births by 2030. Identifying the factors of U5M may be useful for designing targeted and area-specific interventions to accelerate the reduction of childhood mortality. Objective: This study is conducted to identify the factors affecting the survival status of under-five children in selected districts of Nepal. Materials and Methods: Primary data collected through a structured questionnaire were analyzed in this study. In total, 205 live-born children younger than five years before data collection from the selected areas were included in this study. To explore the factors affecting the survival status of under-five children, a multivariable logistic regression model (MLRM) was fitted. Likelihood ratio test, Hosmer-Lemeshow goodness of fit test were used to examine the fit of the model. Predictive power of the model was evaluated with the Receiver Operating Characteristic curve. Results: After fitting the MLRM, different factors were found to be significantly associated with the survival status of under-five children. Muslim mothers as compared to Brahmin and Chhetri (AOR = 10.21, 95% CI: 1.42 - 73.30), the unhealthy child at the time of birth than those who were healthy (AOR = 19.25, 95% CI: 2.00 - 185.04), mothers who had no education as compared to those having secondary and higher level (AOR = 14.59, 95% CI: 1.65 - 128.88), children who had smaller or larger than average size at birth in contrast to those having average size (AOR: 3.49, 95% CI: 1.02 - 12.00), children from households that uses wood as a cooking fuel relative to those using LPG (AOR = 32.20, 95% CI: 7.78 - 133.22) more likely to experience U5M. Whereas, children whose fathers had no education, compared to those having secondary and higher education, had a lower risk of U5M (AOR = 0.048, 95% CI: 0.004 - 0.47). Conclusion: Ethnicity of mothers, health status of child at the time of birth, mother’s education, size of child at birth, father’s education, and types of cooking fuel were the key factors related to survival status of under-five children. Advancing women’s education to at least the secondary level, encouraging and supporting communities for the use of clean energy, and strengthening the systems that provide a continuum of care and adequate treatment for infants born with vulnerable health are the important tasks to reduce U5M in the study areas.